Visitor Satisfaction Level Towards Facility Management at Lubuk Timah Recreation Center, Ipoh - Ishak, Syahidaton Akma; Omar, Abdul Jalil (Research in Management of Technology and Business, 2025)
This study was conducted to evaluate visitor satisfaction with the management of facilities at Lubuk Timah Recreation Center. The objectives were to identify the facility management process and the level of visitor satisfaction with the facility management at Lubuk Timah Recreation Center, including the factors influencing satisfaction and assessing the effectiveness of the provided facilities. Data were collected using qualitative methods, namely interviews and surveys. Interviews were conducted with the recreation center manager, while the survey involved 100 respondents who visited the center. Thematic analysis was used for interview data, while descriptive statistics were applied to the survey data to identify the relationship between cleanliness, safety, and accessibility with visitor satisfaction. The findings revealed that the majority of visitors were satisfied with the facility management, particularly in terms of cleanliness and safety. However, issues such as insufficient parking spaces and facility maintenance were highlighted and require attention from the management. This study provides recommendations for improving facility management to ensure a better recreational experience and support efforts to promote Lubuk Timah as a premier recreational destination.